Effect of autoclaving and cooking on phenolic compounds in buckwheat-enriched whole wheat tagliatelle. (November 2015) - Jambrec, Dubravka; Sakač, Marijana; Mišan, Aleksandra; Mandić, Anamarija; Pestorić, Mladenka
Abstract: The effect of buckwheat achene autoclaving on the phenolic content of the flour obtained by grinding was investigated. The potential of obtained flour to improve the phenolic profile of common whole wheat tagliatelle, and cooking quality, expressed by the amount of phenolics loss during pasta cooking, were also studied. Autoclaving reduced free, but increased bound phenolic forms in flour and tagliatelle samples. Moreover, it reduced rutin conversion into quercetin in great extent during production of tagliatelle with autoclaved buckwheat flour while during cooking of these samples conversion did not occur. The loss of phenolic compounds from buckwheat-enriched whole wheat tagliatelle during cooking (48.1–61.1%) was in the range of the control sample (57.6%) indicating that pasta containing buckwheat flour may maintain cooking quality. Highlights: Tagliatelle was enriched with autoclaved and common whole buckwheat flour. The autoclaving increased bound phenolic form in tagliatelle samples. The autoclaving increased ferulic acid and catechin content in tagliatelle samples. The autoclaving reduced rutin conversion in uncooked and cooked tagliatelle samples. The autoclaving slightly decreased phenolics losses during tagliatelle cooking.